2015
DOI: 10.1130/g36477.1
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch of glacier extent and summer insolation in Southern Hemisphere mid-latitudes

Abstract: Here we address a long-standing puzzle of ice-age climate called the "fly in the ointment of the Milankovitch theory." Using geomorphic mapping and 10 Be surface-exposure dating, we show that five moraine belts were formed during maxima of the last ice age by the Pukaki glacier in New Zealand's Southern Alps. They afford ages of 41.76 ± 1.09 ka, 35.50 ± 1.26 ka, 27.17 ± 0.68 ka, 20.27 ± 0.60 ka, and 18.29 ± 0.49 ka. These five maxima spanned an entire precessional cycle in summer insolation intensity at the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 28 publications
7
53
1
Order By: Relevance
“…The first is that many Southern Hemisphere climate proxies, including Antarctic temperature records, suggest glacial-interglacial climate change occurred broadly in-phase between the Southern and Northern Hemispheres, despite covariance of summer insolation (Mercer, 1984;Jouzel et al, 2007;Wolff et al, 2010a;Huybers & Denton, 2008). Secondly, glacial activity prior to the gLGM, as observed in our compiled chronology, is at odds with a model in which conditions suited to maximum ice growth occurred during the gLGM (Barrows et al, 2007a;Wolff et al, 2009;Doughty et al, 2015). One explanation is that, for the Southern Hemisphere, the duration of seasons may exert a greater control on climate than insolation intensity (Huybers & Denton, 2008).…”
Section: Insolation Changesmentioning
confidence: 75%
See 3 more Smart Citations
“…The first is that many Southern Hemisphere climate proxies, including Antarctic temperature records, suggest glacial-interglacial climate change occurred broadly in-phase between the Southern and Northern Hemispheres, despite covariance of summer insolation (Mercer, 1984;Jouzel et al, 2007;Wolff et al, 2010a;Huybers & Denton, 2008). Secondly, glacial activity prior to the gLGM, as observed in our compiled chronology, is at odds with a model in which conditions suited to maximum ice growth occurred during the gLGM (Barrows et al, 2007a;Wolff et al, 2009;Doughty et al, 2015). One explanation is that, for the Southern Hemisphere, the duration of seasons may exert a greater control on climate than insolation intensity (Huybers & Denton, 2008).…”
Section: Insolation Changesmentioning
confidence: 75%
“…This suggests that the same forcing factors may have controlled the timing of glacial activity in both regions over the last glacial cycle and strongly suggests that glaciers advanced by at least 45 ka, or mid-MIS 3, well before the gLGM. Although this study focuses on chronology, it is worth highlighting that several studies found the limits relating to these advances to be as extensive, if not significantly more extensive, than those deposited during the gLGM (Glasser et al, 2011;Putnam et al, 2013b;Kelley et al, 2014;Rother et al, 2014;Doughty et al, 2015;Darvill et al, 2015;Schaefer et al, 2015).…”
Section: Evidence From the Compilation Of Exposure Agesmentioning
confidence: 99%
See 2 more Smart Citations
“…The tropical Pacific Ocean also modulates circulation dynamics, precipitation amounts, and temperature in the Andes, and may have influenced western Andean ranges differentially over time . Other work in New Zealand and mid-latitude Chilean Lakes district (Doughty et al, 2015) also show a decoupling of glacier advances from local summer insolation that seems convincingly to pace the large Northern hemisphere ice sheets. In contrast, these southern mid-to-high-latitude sites suggest that glacier extent during the last termination was aligned with Southern Ocean surface temperature and with atmospheric carbon dioxide.…”
Section: Discussion: Synthesis Of Dates and Climate Eventsmentioning
confidence: 75%